First experiences to build the Colombian Advanced Computing Network: LaRedCCA - Torres Niño, Luis Alejandro (ACI Avances en Ciencias e Ingenierías, 2021)
The Colombian Network for Advanced Computing (LaRedCCA) was established to strengthen the supercomputing community and unite knowledge, resources, and infrastructure geographically distributed in Colombia through the academic network. It also seeks to integrate high-performance computing resource centers to support scientific and academic initiatives of national interest and not for profit. It has been initially formed by the SC3UIS (Supercomputing and Scientific Calculation) of the Industrial University of Santander, the University of the Andes, and the National Academic Network for Advanced Technology (RENATA). The RedCCA has established an initial test bed to share computing resources through a high-speed link provided by RENATA and seeks to support research in all areas of the country's scientific and technological ecosystem, promoting areas such as parallel and distributed computing, artificial intelligence, and Big Data. This link has shown interesting results by providing a dedicated HPC channel that provides high bandwidth for data transfer for subsequent analysis or simulations performed by the research centers of the Universidad de Los Andes in and on high computing resources. SC3UIS performance, mainly on the GUANE-1 platform.
Keywords: High-Performance Computing Centers; Academic Networks; Networking